Seasonal activity of hexapods in woodland and forest leaf litter in the south-west of Western Australia - Majer, Jonathan; Koch, L. (1982)
Invertebrates were collected in pitfall traps monthly between March 1976 and February 1977 at 3 localities in the south-west of Western Australia, namely Perth (Reabold Hill), Dwellingup and Manjimup. The Collembola and Insecta are treated here.Herbivore diversity was high in spring, summer and early autumn at Perth, and in summer and early autumn at Manjimup; although diversity fluctuated less with season at Dwellingup it was lower in the winter. Predator and parasite diversity was highest in late autumn and early spring at Perth and Manjimup, but seasonal trends again were less obvious at Dwellingup. The numbers of individuals and species of ant were low in winter, increased in spring and summer, and decreased again towards the end of autumn at Perth and Dwellingup. At Manjimup, the seasonal activity of ants was less marked although more species were active in summer. Most Collembola species were trapped in Perth in winter, and in autumn, winter and spring at Dwellingup; but the Manjimup data are insufficient for interpreting.The data from this paper are combined with those of Koch and Majer (1980) on non-hexapod groups collected at the same time. The 3 sites had different phenological patterns and this was particularly marked at Maniimup where temperatures are lower and relative humidities higher.